LAGOA DO PORTINHO IN PARNAÍBA, PIAUI, BRAZIL: EVALUATION OF THE INFRAESTRUCTURE AND TOURIST ATTRACTIONS - Araujo, Keline Medeiros de; Oliveira, Deyse Cristina Castro de; Rocha, Juliana Rodrigues; Rocha, Jefferson Almeida; Silva, Jurandy do Nascimento; Oliveira, Stefan Vilges de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Tourism may be regarded today as the biggest industry of the world and ecotourism is a branch of this industry that grows around 20% per year. Brazil is known for providing the highest number of attractions for all profiles of ecotourist and conditions for the most diverse forms of ecotourism. In this context there are few studies on Lagoa do Portinho in the Parnaiba Delta, in the state of Piauí. The objective of this study was to evalute the infrastructure, touristics attractions and identify positive and negative impacts on local tourism. A descriptive study of local resources was developed, where the seek for details was made by questioning and remarks. The results showed that the region has good infrastructure 54.28% and 42.85% of those surveyed reported seeing as good the offer of tourists attractions. However, 38.57% reported that the cleaning and disposing of garbage was merely regular. Therefore we concluded that the region is able to receiving tourists, it offers good options for leisure and satisfactory infrastructure. However is required investiments for proper disposal of garbage.